2005
DOI: 10.1107/s0021889804030675
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the mosaic structure of an ordered (Al,Ga)N layer

Abstract: The mosaic structure of an (Al, Ga) N layer grown on (0001) sapphire showing natural ordering was studied by high-resolution X-ray diffraction (HRXRD) reciprocal-space mapping. The direction-dependent mosaicity of the layer has been elaborated using maps of symmetrical and asymmetrical reflections. The reciprocal-lattice points show significant broadening depending on the direction in reciprocal space, the diffraction order and the reflection type ( fundamental or superstructural). The evaluation followed two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 31 publications
(42 reference statements)
0
22
0
1
Order By: Relevance
“…2,3 It has recently been shown that III-nitride layers grown on an Al 2 O 3 ͑0001͒ substrate have a predominantly mosaic structure consisting of c-oriented nanocolumns. 4,5 Furthermore the size dependence of Young's modulus has been revealed in nanocolumn structures, such as ZnO nanowires with a diameter of Ͻ120 nm ͑Ref. 6͒ or GaN nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 It has recently been shown that III-nitride layers grown on an Al 2 O 3 ͑0001͒ substrate have a predominantly mosaic structure consisting of c-oriented nanocolumns. 4,5 Furthermore the size dependence of Young's modulus has been revealed in nanocolumn structures, such as ZnO nanowires with a diameter of Ͻ120 nm ͑Ref. 6͒ or GaN nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note here that the diffraction peaks are not Gaussian in shape. However, as was shown in the experimental and theoretical investigations performed in recent years [5,6,17,18], they are approximated in the central part by the Voigt function with a certain fraction of the Lorentzian contribution, and the intensity on the wings of the peaks decreases more rapidly and, in the majority of the cases, as a power function. In this case, the law of decay in the intensity on the wings and the fraction of the Lorentzian broadening depend on the character of the distribution of the dislocations.…”
Section: Resultsmentioning
confidence: 91%
“…XRD APD detection has also been applied in thin films for AlGaN on sapphire [8], GaAs on Si [9] and GaP on Si [10]. The idea is that weak ''antiphase'' reflections (APR) act as APD sensors.…”
Section: Introductionmentioning
confidence: 99%